Observing the spread of Agulhas Leakage into the Western South Atlantic by tracking mode waters within ocean rings - Guerra, Luiz Alexandre A.; Mill, Guilherme N.; Paiva, Afonso M. (Frontiers in Marine Science, 2022)
The Agulhas rings transport warm and salty waters that feed the surface limb of the Atlantic Meridional Overturning Circulation. Some studies have focused on the conveying capacity of ocean eddies, and recently, the role of the Agulhas rings in advecting water masses and organisms has been explored. Here we show evidence that the Agulhas rings are responsible for the advection of mode waters from the Cape Basin to the western side of the Atlantic. We analyzed more than 3,200 temperature profiles and 2,400 salinity profiles from historical databases collocated with 52 long-lived Agulhas rings tracked from 1993 through 2016. An automated algorithm was used to identify thermostads in the profiles acquired within the rings. The data revealed mode water layers trapped inside 88% of the rings. The joint distribution of temperature and salinity indicated two types of mode waters in the range 16.2 ± 0.6°C, 35.6 ± 0.1 (Type I) and 12.9 ± 0.7°C, 35.2 ± 0.1 (Type II). The majority (67%) of the rings carrying mode waters had both types detected inside. Moreover, considering only those rings sampled west of the Mid-Atlantic Ridge, we found that 45% of them advected mode waters to the western basin. Therefore, our results demonstrate that, despite the long journey, interaction with the bottom topography and other vortices, ocean-atmosphere exchanges, and decay, the Agulhas rings are responsible for spreading mode waters initially available at the Cape Basin throughout the South Atlantic, contributing to a positive anomaly in temperature and salinity along the eddy corridor joining the Cape Basin to the Brazil Basin.